Effect of the volume fraction of the ex-situ reinforced Ta additions on the microstructure and properties of laser-welded Zr-based bulk metallic glass composites. (January 2016) - Wang, Huei-Sen; Wu, Jyun-Yi; Liu, Yi-Ting
Abstract: To investigate the effect of the volume fraction of the ex-situ reinforced Ta additions on the weldability of Zr–Cu–Ag–Al bulk metallic glass composites (BMGCs), in this study, different Ta contents (0–6 vol%) of BMGCs are welded using the Nd:YAG pulsed laser technique with preselected welding parameters. After welding, the microstructure (including the parent material (PM), weld fusion zone (WFZ) and heat-affected zone (HAZ)), mechanical and thermal properties of the test samples are investigated. The test results show, for all BMGC welds, the micro-sized Ta particles in the PM, WFZ and HAZ to be covered by a crystallized interfacial layer (IL), ZrCu. For both un-welded and laser-welded BMGCs, as the Ta contents increase, the glass transformation temperature (Tg ) increases, which in turn reduces the glass formation ability (GFA) indices, ΔTx, γ and γm . However, when compared to that of un-welded BMGC, the GFA index, ΔTx, of the laser-welded BMGCs is slightly improved. However, the γ, and γm of the BMGC welds seem not to be affected. In addition, due to the characteristics of the rapid thermal cycle of the laser welding process, two smaller sizes of Ta, nano-sized (mainly on the surface of WFZ) and sub micro-sized Ta, are found in the WFZ. These sub-micro-sized Ta particles normally locate near the micro-sized Ta, which tends to slightly reduce the hardness in this area. Furthermore, an increase in the volume fraction of Ta (0–6 vol%) in the BMGCs does not encourage the formation of the harmful crystalline phase in the amorphous matrix after the laser welding process. It is observed that, other than the IL (ZrCu) on the micro-sized Ta particles, no other type of crystalline is observed in the amorphous matrix of the laser-welded BMGCs. Highlights: Various ex-situ Ta contents of BMGCs were laser welded with preselected parameters. Microstructure, mechanical and thermal properties of the welds were investigated. Increased Ta contents results in reduction of GFA in BMGC and BMGC welds. No harmful crystalline formed in amorphous matrix of the BMGC welds. All welded BMGCs still have good thermal and mechanical properties.